The effectiveness of pregnancy exercises for a smooth childbirth process - Islami, Thoyibatul; Ismarwati (Universitas Airlangga, 2025)
HIGHLIGHTS Pregnant women are prone to experiencing labor jams and tears during childbirth Regular pregnancy exercises during the third trimester of pregnancy can help the delivery process run smoothly and reduce the occurrence of birth canal tears. ABSTRACT Objective: Childbirth is the process of delivering the fetus, placenta, and membranes from the uterus through the birth canal. It requires both physical and psychological preparation to ensure a safe and smooth delivery. This study examined the effectiveness of pregnancy exercises in facilitating a smoother labor process. Materials and Methods: This study employed a systematic review method, utilizing databases such as PubMed, ScienceDirect, ProQuest, Wiley Online Library, and EBSCO. Article selection followed the PICO framework, using keywords like